(3eHGOF GdeMGSHI GdeGdjI (B:s (3GdCSS GdYdejI aj GdbjGS GdeMGSHj (B/s - (3GdUaGQ, gGOj QVGs ((3YeGf(B: s (3OGQ GdKbGaI ddfTQ hGdJhRjY(B, s, 2006)
(3fThA GdeMGSHI hJWhQgG, GdfXGe GdeMGSHj hGdOhQI GdeMGSHjI, GdYedjGJ GdJehjdjI, GdYedjGJ GdEjQGOjI, GdYedjGJ GdQCSeGdjI, aJQI GdMSGHGJ GdNJGejIs
(3HHdjhZQGajG(B: (3U(B.397s
Keywords: (3GdEOGQI GdeGdjIs; (3GdeMGSHIs